2015
DOI: 10.1039/c5nr01499a
|View full text |Cite
|
Sign up to set email alerts
|

A magnonic gas sensor based on magnetic nanoparticles

Abstract: In this paper, we propose an innovative, simple and inexpensive gas sensor based on the variation in the magnetic properties of nanoparticles due to their interaction with gases. To measure the nanoparticle response a magnetostatic spin wave (MSW) tunable oscillator has been developed using an yttrium iron garnet (YIG) epitaxial thin film as a delay line (DL). The sensor has been prepared by coating a uniform layer of CuFe2O4 nanoparticles on the YIG film. The unperturbed frequency of the oscillator is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…[52][53][54][55][56] That is to say, analyzing the change in magnetic properties of substrates upon interaction with gases could be a new way to detect gases. For example, Matatagui et al 55,56 reported the combination of a magnetostatic surface wave oscillator with a layer of magnetic oxide nanoparticles in what they called a magnonic gas sensor. The perturbation of the magnetic properties of the magnetic oxide layer induces a frequency shi in the magnetostatic surface wave oscillator that can be registered in the presence of different gases.…”
Section: à22mentioning
confidence: 99%
“…[52][53][54][55][56] That is to say, analyzing the change in magnetic properties of substrates upon interaction with gases could be a new way to detect gases. For example, Matatagui et al 55,56 reported the combination of a magnetostatic surface wave oscillator with a layer of magnetic oxide nanoparticles in what they called a magnonic gas sensor. The perturbation of the magnetic properties of the magnetic oxide layer induces a frequency shi in the magnetostatic surface wave oscillator that can be registered in the presence of different gases.…”
Section: à22mentioning
confidence: 99%
“…To overcome such limitation, the surface of Fe 3 O 4 nanoparticles was coated by alumina because of desired point of zero charge (pzc = 9.3) (Xu et al 2014). For example, the modified magnetic nanoparticles, as coated form, were used for high sensitive determination of volatile organic carbon compounds (Matatagui et al 2015). The MNP adsorbents, have a high surface area-to-volume ratio and good superparamagnetic property.…”
Section: Introductionmentioning
confidence: 99%
“…A number of of the magnetic nanostructures can be used in medical applications due to their non-toxicity and biocompatibility [1][2][3]. Several studies have been performed into the use of the materials in drug delivery [4,5], magnetic resonance imaging (MRI) [6], hyperthermia [7,8], medical diagnosis and therapy [9,10] gas sensors [11][12][13], catalysts [14,15], and environmental remediation [16,17]. Several methods are used to synthesize magnetic material; e.g., sol-gel [18,19], reverse micelle [20], co-precipitation process [21,22], γ-ray irradiation [23,24], non-aqueous route [25], microwave plasma synthesis [26], and hydrothermal treatment [27,28].…”
Section: Introductionmentioning
confidence: 99%